PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT DAN INOVASI TERHADAP PERAN KAPABILITAS TEKNOLOGI SERTA DAMPAKNYA PADA KINERJA KARYAWAN (SURVEY PADA PERUSAHAAN COLD STORAGE KOTA MAKASSAR) - Arimansah Sahabuddin; Muhammad Asdar; Syamsul Alam; Jusni Jusni (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2016)
The purpose of this research was to give a empirical evidence and find clarification on the phenomenon influence the application of the total quality management and innovation on the role of capabilities technology and its impact on performance an employee ( Surveyin cold storage companies Makassar City). Methods used is research a survey data collection use kuisioner to know evaluation by respondents employees cold storage companies in the city makassar to variables of the study . As for the kind of research this is deskriptif-verifikatif . The sample size of 260 had been taken by technique random proportional clusters of sampling of the population target about 1236 spread in three companies in the cold storage makassar.To test hypotheses proposed analysis equation used modeling structural or structural equation modeling (SEM ) according to the model composed through model measurement and structural model a causal relation between variables . The implications of the research this is that capability technology is a dominant influence study compared to variable other productivity against employee performance .Variable next innovation having influence that are more dominant , good against technology capabilities and direct influence on productivity of employee performance and indirectly through technology capabilities compared to variable total quality management .